Thinning out spectators: Did football matches contribute to the second COVID-19 wave in Germany? - Fischer, K. (SSRN, 2021)
This paper provides an ex-post analysis of football matches` contribution to the spread of COVID-19 during Germany`s second infection wave in summer and autumn 2020. We find slightly positive effects from occurring professional football matches on newly registered cases of the virus in the respective counties. An upper boundary gives us that an additional match in a county on average raises the number of daily registered cases by up to between 0.52 and 0.91 cases per 100,000 inhabitants after three weeks. Hence, this on average implies an increase in the seven-day incidence per 100,000 inhabitants by up to between 3.6 and 6.4. We do not find qualitatively different results in a subsample of German top league matches which were associated to have the strictest hygiene regulations. Most importantly, the found effect is mediated by the incidence level at the day of the match with very few infections for matches at a seven-day incidence below 25. As an underlying mechanism, we identify increases in the local mobility. Further, infections are not explicitly driven by higher occupancy levels. We finally show that the ban of away fans successfully restricts the spread of COVID-19 beyond county borders and also find indication for a reduced effect from football matches in the presence of the `lockdown light` which Germany launched in early November.